Physiological Predictors of Postoperative Pulmonary Complications in Thoracic Surgery Patients with Cardiovascular Comorbidities: A Cross-Sectional Clinical Study - Imran Tahir, Ahmad Ali, Asad Shameem, Abdur Rauf Hammad, Saleem Shahzad Gondal, Muhammad Yousuf Memon (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Postoperative pulmonary complications (PPCs) are among the most frequent causes of morbidity and prolonged hospitalization following thoracic surgery, particularly in patients with coexisting cardiovascular diseases. Identifying physiological predictors of PPCs can guide preoperative optimization and improve surgical outcomes. Objective: To evaluate key physiological predictors associated with the development of postoperative pulmonary complications in thoracic surgery patients with cardiovascular comorbidities. Methods: This cross-sectional clinical study was conducted at the Department of Thoracic Surgery, MTI–Hayatabad Medical Complex, Peshawar, and THQ Hospital, Kallar Syeda, from March 2022 to March 2023. A total of 120 patients undergoing elective thoracic surgeries were included. Preoperative assessments included spirometry (FEV₁), arterial blood gases (PaO₂, PaCO₂), oxygen saturation (SpO₂), ejection fraction (EF), and body mass index (BMI). All patients were followed for seven days postoperatively for PPCs such as atelectasis, pneumonia, bronchospasm, and respiratory failure. Data were analyzed using SPSS v26, with logistic regression applied to determine independent predictors. Results: The incidence of PPCs was 32.5%. Patients with PPCs had significantly lower mean FEV₁ (58.7 ± 12.1%), EF (46.5 ± 7.4%), and SpO₂ (91.6 ± 3.2%) and higher PaCO₂ levels (48.6 ± 6.1 mmHg). Multivariate analysis identified FEV₁ < 60% predicted (OR 4.12, p = 0.001), EF < 50% (OR 3.56, p = 0.003), BMI > 30 kg/m² (OR 2.21, p = 0.038), and PaCO₂ > 45 mmHg (OR 2.94, p = 0.011) as independent predictors of PPCs. Conclusion: Reduced pulmonary capacity, impaired cardiac function, obesity, and hypercapnia are strong physiological predictors of postoperative pulmonary complications. Incorporating these parameters into preoperative risk assessments can enhance patient safety and postoperative outcomes. Keywords: Thoracic surgery, postoperative pulmonary complications, cardiovascular comorbidities, FEV₁, ejection fraction, obesity, hypercapnia.